Parental knowledge, attitude and practice on malaria in Mandailing Natal district - Syafruddin Haris; Sri Sofyani; Bidasari Lubis; Munar Lubis; Syahril Pasaribu; Iskandar Z. Lubis (Indonesian Pediatric Society Publishing House, 2007)
Background Malaria is still considered to be an important health problem in Indonesia. Malaria has been found in islands with different degree of endemicity. Behavior of the community is one of the factors affecting the incidence of malaria in Mandailing Natal district. Objective To know the parental knowledge, attitude, and practice among parents whose children suffered from malaria or not. Methods A cross sectional study was conducted in six primary schools and one health centre in October 2004. Subjects were parents whose children were malaria positive and malaria negative based on laboratory examination. Sample size was 85 parents for each group. Selected respondents were interviewed using structured questionnaire. Degree of knowledge, attitude, and practice on malaria were established using scoring system within three categories: good, less, and poor. Data were collected and presented using chi-square and P<0.05 was considered as a level of significant. Results The mean age of 85 parents whose children were positive malaria, was 38.47 years (SD 6.67) and the mean age of those whose children were negative malaria was 40.41 years (SD 8.05). Parent's education level was 62.9% primary school and 90% of their children were school-aged. There were significant differences on parental knowledge, attitude and practice in each group (P<0.05). There was also a significant correlation between occupation and knowledge, but not between parental education level and parental age. Parental knowledge and attitude on the incidence of malaria in Mandailing Natal district were good, though their practice were poor. Conclusion There are significant differences on parental knowledge, attitude and practice, between parents whose children were positive and negative for malaria.